Evaluación de la obtención de colorante natural a partir del hollejo de uva (Vitis Vinifera 'Cabernet Sauvignon') y la cáscara de mandarina (Citrus Reticulata) para aplicación en la industria alimentaria. (2021)
This document presents the development and evaluation of the obtaining of dye from mandarin peel and grape skins from a technical approach to the extraction process of carotenoids and anthocyanins respectively; in order to generate value for each of the raw materials with the innovation of natural products that meet the characteristics and specifications of the market. Experimental development was carried out by means of a proximal bromatological analysis in order to analyze the most abundant components present in the samples, and a literature review was carried out comparing similar studies, which defined the conditions of the Soxhlet extraction process as a 96% ethanol solvent, volume-weight ratio of 20:1 and temperature between 60°C and 70°C to avoid degradation of the compounds. of interest, obtaining an average extraction yield of 71.95% for mandarin peel with 1139 μg β-carotene/100 g and 61.57% for grape peel with 23.39 mg cyanidine-3-glucoside/100 g dry matter.